ANALYSIS OF TESTS USING THE WHITEBOX AND BLACKBOX METHODS ON WEB-BASED CAR RENTAL SYSTEMS - Afifah Pendri; Cintia Putri Trisya; Ridho Arif Fandi; Rizky Ayu Mahroja; T. Taufiqul Mannan; Yulia Heriana Putri (Lembaga Riset dan Inovasi Almatani, 2025)
Car rentall is a company engaged in the service sector which provides services in the form of car loans based on predetermined conditions. in this company there are obstacles faced by cv. Prime car rental in Pekanbaru, where the administration still uses paper media and writing is still in the form of documents on car return data, tenant data, and car renter transaction reports. However, with this error several problems often occur which cause a slow process of car rental, data search, and the process of making monthly reports. For this reason, it is necessary to test a web-based car rental information system so that it can be used optimally according to the functions and needs of the company. In solving this problem we use the whitebox and blackbox methods to test the car rental system at Pekanbaru. where is the test that we did to provide an explanation with the results of the system that has been made where, it can be concluded whether the system can help the company.